Diagnosis and treatment of intraspinal lipomas - Dinçer, Fitnat; Gökalp, Hamit Ziya; Dinçer, Cumhur; Zorlutuna, Ahmet (The Turkish Journal of Pediatrics, 1991)
In this article a 32-case series of intraspinal lipoma localized to the lumbosacral region is presented. All of the patients underwent surgery. Recent reports in the literature indicate that although these lesions show advanced and progressive neurological deficits, very good results can be achieved with surgical treatment. The advantages of computed tomography in diagnosis and the importance of early surgical intervention and postoperative rehabilitation are emphasized.